You are on page 1of 5

Gurnett and Bhattacharjee 5.

4
Xuxa Borealis
September 23, 2016
To represent a loss-cone distribution, we sometimes use a distribution of the form
f0 (v , vk ) =
2
2

where C
= T
m and Ck =
5.4a) Show that

Tk
m ,

2
2
vk2
v
v
l
)
exp(
)exp(
)
2
2 C l! 2C 2
2C
2Ck2
(2) C

n0

3
2

(1)

and l is an integer.
Z

v = n0
f0 (
v )d3

(2)

Since our distribution is in terms of the parallel and perpendicular components of the velocity, it behooves
us to define the integral in term of the cylindrical velocity space:
Z
Z
Z
Z 2

3
d v =
dvk
v dv
d
(3)

d3
v =

2v dvk dv

(4)

So plugging in our distribution, f0 (v , vk ), into the integral: [its gonna look messy, and it wasnt fun to
type up in TEXbut we will break it up and find out that it isnt that bad.]
n0 =

2n0
3
2

2 C l!
(2) C
k

exp(

vk2

2 )dvk

2Ck

v (
0

2
v
v 2
)l exp(
2
2 )dv
2C
2C

(5)

Well start with the easier one of the two integrals, the parallel component:
Z

exp(

vk2
2Ck2

)dvk

(6)

Sure you can use what you might know about Maxwellian functions to solve this integral with actual math,
I prefer to use my trusted Schaums Mathematical Handbook of Formulas and Tables, but it is your choice.
The corresponing formula for this form is (18.72)
r
Z
2
1
eax dx =
(7)
2 a
0
Since equ. 6 is an even function it is possible to change the limits to match equ. 7 by just including a factor
of 2, and a = 2C1 2 .
k
Z
q
vk2
1q
2
exp( 2 )dvk = 2(
2Ck2 ) = 2Ck2
(8)
2Ck
2
0
For the second integral, the solution is not as straight forward. From within the parentheses pull out the
power of 2, and then bring the extra v term inside the parentheses, now to the power 2l; resulting in
1
( 2C
)2l (v )2l+1

v (
0

2
v
v 2
1

)l exp(
)2l
2
2 )dv = (
2C
2C
2C

Z
0

(v )2l+1 exp(

2
v
2 )dv
2C

(9)

Now, we cant just go to Schaums this time, I had to do some fancy Googling with some direction from
a classmate. If you Google Integrals with Exponentials Wikipedia gives a great list of intergrals, many
are in Schaums as well. [As of 09/22/16, the important equation is 11th from the bottom.]
Z
2
k!
xn eax dx = k+1
(10)
2a
0
where n = 2k + 1, k is an integer, and a > 0. For our problem k = l, so n = 2l + 1 and [hey!] that is what
we have. Now, use the equation!
Z
1
v 2
1
l!
2l+1
2l

v
(11)
(
)
exp(
)2l
1
2 )dv = (
2C
2C
2C 2( 2C 2 )l+1
0

Awesome, now to put the pieces together and do algebra.


q
1
2n0
l!
2Ck2 (
)2l
3
1
2
2
2(
)l+1
2C
(2) C Ck l!

2C 2

(12)

Cancelling the l!
2n0
(2)

3
2

2C
C
k

2Ck2 (

1
1
)2l
1
2C 2( 2C 2 )l+1

(13)

Rearrange to see that the 2 and Ck values also cancel out.


2

(2) 2 (2) 2 (2)

3
2

n0 Ck
1
1

)2l
1
2C (
C
2(
)l+1
2C
k
2C 2

(14)

The next equations are me just typing out the algebra that I did.
1
n0
1

)2l
2 (
C
2C 2( 2C1 2 )l+1

(15)

2
n0 C
(2

1
2

2
n0 C
(2

1 2l 1 1 2 l1
C
) 2 (2 C )
1
2

1 2l 1 l+1 2l+2
C
) 2 2 C

(16)
(17)

2 2l 2l+2 l 1 l+1
n0 C
C C 2 2 2

(18)

22l+2+2l l1+l+1
n0 C
2

(19)

n0

(20)

Ta-Da!
5.4b) Show that

P = 0
0

0
0
Pk

0
P
0

where P = (l + 1)n0 T and Pk = n0 Tk .


We are still working in cylindrical velocity space, like part (a) of this problem, so
Z
Z
Z

d3
v =
dvk
2v dv

(21)

(22)

From the text (equ. 5.1.7) the pressure is defined as


Z

Ps = ms (
v Us )(
v Us )fs (
v )d3 v

(23)

Again, like part (a) it helps to work in terms of k and .


Z

2
P = m
v
f0 (
v )d3
v

(24)

vk2 f0 (
v )d3
v

(25)

2
2
vk2
v
v
l
)
exp(
)exp(
)
2
2 C l! 2C 2
2C
2Ck2
(2) C

(26)

Pk = m

Below is nothing new it is just a reprint of equ. (1)


f0 (v , vk ) =

n0

3
2

We will start with the Pk because its simpler. So plug f0 (v , vk ) in to the equation for Pk .
Pk =

(2)

3
2

2n0 m
2 C l!
C
k

vk2 exp(

vk2

v (

2 )dvk

2Ck

2
v
v 2
)l exp(
2
2 )dv
2C
2C

(27)

Now, solve this mess one integral at a time, starting with the k part

vk2 exp(

vk2
2Ck2

)dvk

(28)

Time to visit our good ol Schaums, equ. 18.77. We are forced to fight the dreaded Gamma Function, ,
this time, no tricks... at least not the way I am doing it. Below is the equation from Schaums:

xm eax dx =

[ (m+1)
]
2
2a

(29)

(m+1)
2

Since equ. 28 is an even function it is possible to change the limits to match equ. 29 by just including a
factor of 2, and a = 2C1 2 .
k

vk2

vk2 exp(

2
0

2 )dvk = 2(

2Ck

[ (2+1)
2 ]
2( 2C1 2 )

)=
(2+1)
2

[ 32 ]
3

( 2C1 2 ) 2

(30)

Here is some pedantic algebra for you to gorge on (or get completely annoyed by):
[ 32 ]
3
( 2C1 2 ) 2
k

3
3
= [ ](21 Ck2 ) 2
2

(31)

3 3
[ ](2 2 Ck3 )
(32)
2
Now for a quick Google session: Gamma Functions. Head to Wolfram MathWorld, and there you will find a
whole bunch of information, including
information we will need a little later so remember this page. At this
point, go down to equ. 56: ( 32 ) = 12 . Now equ. 32 becomes:
3
1
(2 2 Ck3 )
2

More boring algebra:


2
OK!! So now we have that

2
2

vk2 exp(

(2 2 Ck3 ) = 2 2

vk2
2Ck2

)dvk =

v (
0

Ck3 =

(33)

2Ck3

(34)

2Ck3 . On to the next integral.

2
2
v
v
l
)
exp(
2
2 )dv
2C
2C

(35)

Okay we are going to start by doing the same rearrangement that we did at equ. 9. You will also see that
this integral is exactly the integral from part (a), equ. 11, so we can take those results.
Z
1
v 2
2l+1
( 2 )2l
v
exp(
(36)
2 )dv
2C
2C
0
3

1
l!
)2l
1
2C 2( 2C 2 )l+1

(37)

Now we have the results of both of the integrals now to put them all together with the fraction that was not
2n0 m
, the result of equ. 34, and equ. 37 together.
part of the integrals. So put
3
2
(2) 2 C Ck l!

Pk =

(2)

3
2

2 C l!
C
k

2(Ck3 )((

1
21 l!
)2l 1 l+1 )
2C ( 2C 2 )

(38)

3
2

2
2

Pk =

2n0 m

1
2

2 (2) (2) n0 m 3
1
21 l!
)2l 1 l+1 )
(Ck )((
2
C Ck l!
2C ( 2C 2 )

(39)

In the above equation, we are cancelling out the 2 terms, one of the Ck terms, and the l! term.
Pk =

n0 m 2
1
21
2l

(C
)((
)
)
k
2
C
2C ( 2C1 2 )l+1

(40)

The answer is starting to look less messy. Now for some Algebra.
2
Pk = n0 m(C
)(Ck2 )(2

2
Pk = n0 m(C
)(Ck2 )(2
2
Pk = n0 m(C
)(Ck2 )(2

1
2

1
2

1
2

21
2 l+1
(21 C
)

(41)

21
2l1
(2l1 )(C
)

(42)

1 2l
C
)

1 2l
C
)

1 2l 1
2l+1
C
) (2 )(2l+1 )(C
)

(43)

2
2l
2l+1
Pk = n0 m(Ck2 )(C
)(2l )(C
)(21 )(2l+1 )(C
)

(44)

Now... CANCELL, CANCELL, CANCELL!!


Pk = n0 m(Ck2 )
Looking good, recall Ck2 =

Tk
m ,

(45)

and plug that in


Pk = n0 m(

Tk
)
m

(46)

Pk = n0 Tk

(47)

Now it is important to note that Pk = Pzz , so Pk = n0 Tk is the exact result for the pressure tensor.
TA-DA! - part 1
Now to the P equation
Z

2
v
f0 (
v )d3
v

P = m

(48)

So plug f0 (v , vk ) in to the equation for P .


P =

2n0 m
3
2

2 C l!
(2) C
k

exp(

vk2

)dvk
2Ck2

Z
0

3
v
(

2
v
v 2
)l exp(
2
2 )dv
2C
2C

(49)

Once again we will start with the parallel part, which, hey! This integral is the same as in part (a), equ. 6.
The result is in equ. 8.
Z
q
vk2
exp( 2 )dvk = 2Ck2
(50)
2Ck

Okay, to the second integral, we are going to start by doing the same rearrangement that we did at equ. 9.
Z
1
v 2
2l+3
( 2 )2l
v
exp(
(51)
2 )dv
2C
2C
0
4

So now we are back to something the form of equ. 18.77 from Schaums (and equ. 29 above). So back to
Gamma Functions. (Told you to remember that webpage) Using equ. 18.77/29 we get
(

[ (2l+3+1)
]
[ (2l+4)
]
1
1
1
[l + 2]
2
2
= (
= (
)2l
)2l
)2l
(2l+3+1)
(2l+4)
1
1
2C 2( 2 ) 2
2C 2( 2 ) 2
2C 2( 2C1 2 )(l+2)
2C

2C

(52)

This time equ. 1 from the webpage is what you want, (n) = (n 1)!. Using this definition, the mess of a
fraction above becomes
1
(l + 1)!
(
(53)
)2l
2C 2( 2C1 2 )(l+2)

Now for something completely different... NOT! More algebra:


(

1
1
(l + 1)!
1
1
2l+4
2l (l + 1)!2

)2l
=
(
)
)2l (l + 1)!21 2l+2 C
= (
2 (l+2)
2l4
1
l2
2C 2(2 C )
2C 2
2C
C

(54)

1
2l+4
)2l (l + 1)!2l+1 C
2C

(55)

(
(2

1
2

1 2l
2l+4
C
) (l + 1)!2l+1 C

(56)

2l
2l+4
(2l )(C
)(l + 1)!(2l+1 )(C
)

(57)

4
2(C
)(l + 1)!

(58)

Now we have the results of both of the integrals now to put them all together with the fraction that was not
2n0 m
, the result of equ. 50, and equ. 58 together.
part of the integrals. So put
3
2
(2) 2 C Ck l!

P =
2

2n0 m
3
2

2 C l!
(2) C
k

P = (2) 2 (2)
Now... CANCELL

3
2

q
4
2Ck2 (2(C
)(l + 1)!)

2 1
4
(2) 2 n0 mC
Ck Ck (2)(C
)(

(l + 1)!
)
l!
(l + 1)!
2
P = n0 m(2)(C
)(
)
l!

2
4
P = n0 mC
(2)(C
)(

(l + 1)!
)
l!

(59)

(60)

(61)
(62)

It is known that ( (l+1)!


l! ) = (l + 1) so our P becomes
2
P = 2n0 m(C
)(l + 1)

At this point it is important to note: Pxx = Pyy =


not sure if I am missing something but...
TA-DA!

P
2

(63)

This is as close as I could get to the answer. I am